QuILL: innovation and quality in language learning in higher education - Silva, Elisabete Mendes (2021)
The European project QuILL – Quality in Language Learning –, written and coordinated by Pixel-Italy in cooperation with the project applicant and scientific coordinator, Polytechnic Institute of Bragança (IPB)-Portugal, is funded by the Erasmus+ programme, KA2 – Strategic Partnerships for Digital Education Readiness. Other partner institutions participating in the project are Vilnius University, Faculty of Philology, (Lithuania); Cuza University of Iaşi, Department of Language Learning, (Romania); University of Bologna (Italy); Károli Gáspár University (Hungary); and Universidad de Cordoba (Spain). QuILL aims to provide language lecturers with the skills to identify, assess, use, and create digital and ICT based language teaching resources, as well as provide decision makers and policy makers with the information and skills to enhance the implementation of digital and ICT based language teaching sources and methods in the higher education systems. Besides the creation of a database of on-line open educational resources (OER) for language teaching and learning of 18 European languages, QuILL will also create an on-line training package for the identification, use and creation of ICT based language teaching sources for teaching languages at higher education level. In addition, it will publish a document aimed at analysing the technological potential for language learning in European higher education systems. The aims of this paper are two-fold. On the one hand, we intend to introduce the project to the higher education community. On the other, underlying the first intellectual output (IO1) – creation of a database of on-line language learning resources –, we aim to present some of the resources collected, assessed and validated by means of case studies, analysing the type of resources, the methods suggested and applied in the learning-teaching context, highlighting their relevance within the project’s goals. Therefore, we shall attempt to reach some conclusions regarding this innovative and far-reaching process of identification and validation of teaching resources by pointing out their benefits, as well as shortcomings, and their importance in the higher education teaching-learning language context. Not only will it benefit the lecturers, because they will have a wide variety of OER teaching resources available to be used in class, but also the students who can use the resources to learn the selected language in a rather autonomous way.